10.1016/s0029-7437(10)70166-x (CrossRef Listing of Deleted DOIs, 2000)
Aim To investigate the understanding, approach, and experience of fertility preservation counseling among oncology healthcare providers in Iraq in treating reproductive age cancer patients. Methods We have performed a qualitative study with semi-structured face-to-face interviews with 27 healthcare providers who had been engaged in cancer care, such as oncologists and clinical pharmacists. Interviews were conducted to examine the level of awareness on fertility preservation, the existing counseling practice, the referral pathways, cultural factors, and perceived barriers. Transcription of audio-recorded interviews was done verbatim followed by inductive thematic analysis. Results The healthcare providers were mostly aware of the need to talk about fertility preservation prior to cancer therapy, particularly in younger patients. Still, practice was uneven. They identified seven themes, which included awareness and understanding of fertility preservation; attitudes and beliefs; current counseling and referral practices; communication and patient education; cultural, religious, and financial influences; role of pharmacists and multidisciplinary care; and barriers and needs for improvement. The discourse of fertility preservation tended to rely on the personal initiative of clinicians and not on systematic channels. The main obstacles were low local fertility care, urgency in treatments, cost, ineffective referral systems, and embarrassment to talk about reproduction in a conservative environment. Conclusion Fertility preservation awareness is present in this setting, although the implementation is uneven. To make fertility preservation a component of standard cancer care, more practical referral pathways, culturally sensitive educational resources, more explicit team roles, and enhanced cooperation between oncology and fertility services are required.